Analisis Tenses yang Digunakan dalam Film Kung Fu Panda 3: Relevansi terhadap Kurikulum 2013 untuk Pengajaran Tenses pada Siswa SMP/MTs - Agus Wilson (SAP (Susunan Artikel Pendidikan), 2021)
This study aims to find out the tenses used in the film script Kung Fu Panda 3 and its relations between the Curriculum 2013 in tenses learning for junior high school students. The Curriculum 2013 is used as a standard guide to determine the suitability of sentences. This research is descriptive qualitative research using content analysis techniques to analyze the data. Data source Documented film scripts and English Curriculum 2013 for junior high school. The study results are presented in the form of sentences that are analyzed and classified into six types of tenses. The six tenses are in accordance with the Curriculum 2013, namely Simple Present Tense, Simple Past Tense, Present Continuous Tense, Past Continuous Tense, Present Perfect Tense, and Present Future Tense. The study results show a high frequency of relevance to tenses located in film scripts and the Curriculum 2013, with a total of 100%. The results of this study show that the script of the Kung Fu Panda 3 film can be used as a support material for English teachers to teach tenses to junior high school students.